Who should provide care for patients receiving palliative chemotherapy? A qualitative study among Dutch general practitioners and oncologists - Jan Wind; Ineke C. Nugteren; Hanneke W. M. van Laarhoven; Henk C. P. M. van Weert; Inge Henselmans (Taylor & Francis Group, 2018)
Introduction: While close collaboration between general practitioners (GPs) and hospital specialists is considered important, the sharing of care responsibilities between GPs and oncologists during palliative chemotherapy has not been clearly defined. Objective: Evaluate the opinions of GPs and oncologists about who should provide different aspects of care for patients receiving palliative chemotherapy. Design: We conducted semi-structured interviews using six hypothetical scenarios with purposively sampled GPs (n = 12) and oncologists (n = 10) in the Netherlands. Each represented an example of a clinical problem requiring different aspects of care: problems likely, or not, related to cancer or chemotherapy, need for decision support, and end-of-life care. Results: GPs and oncologists agreed that GPs should provide end-of-life care and that they should be involved in decisions about palliative chemotherapy; however, for the other scenarios most participants considered themselves the most appropriate provider of care. Themes that emerged regarding who would provide the best care for the patients in the different scenarios were expertise, continuity of care, accessibility of care, doctor-patient relationship, and communication. Most participants mentioned improved communication between the GP and oncologist as being essential for a better coordination and quality of care. Conclusion: GPs and oncologists have different opinions about who should ideally provide different aspects of care during palliative chemotherapy. Findings raise awareness of the differences in reasoning and approaches and in current communication deficits between the two groups of health professionals. These findings could be used to improve coordination and collaboration and, ultimately, better patient care as results demonstrated that both disciplines can add value to the care for patients with advanced cancer.Key points This study identified contrasting opinions of GPs and oncologists about who should provide different aspects of care for patients receiving palliative chemotherapy. Important themes that emerged were expertise, continuity of care, doctor-patient relations, accessibility of care, and communication. Although frequently using the same arguments, GPs and oncologists often considered themselves to be the most appropriate providers of palliative care.